Model Pendidikan Agama Islam dalam Rehabilitasi Pecandu Narkoba di Pondok Pesantren Tetirah Dzikir Sleman Yogyakarta - Toha Machsun (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2020)
This study aims to describe the rationale for the importance of rehabilitation of drug addicts using islamic religious education and the islamic religious education model used for the rehabilitation of drug addicts in pondok pesantren Tetirah Dzikir Sleman Yogyakarta. This research uses a qualitative approach to the type of case study. The results showed that: (1) The rationale for the importance of rehabilitation of drug addicts using Islamic religious education, includes: juridical, religious, and psychological reasons; (2) The Islamic Religious Education Model in the rehabilitation of drug addicts is carried out in three stages: first, pre-education, second, Islamic education, includes guidance for prayer, fasting, dzikir, qiyamul lail, repentance bathing, religious lectures, learning akidah morals, fiqh, reading and writing the al-qur’an, and the third is post-recovery education. The author argues that in addition to treatment and / or treatment through medical rehabilitation, the healing process for drug addicts can be supported through a religious approach organized independently by the community. The author recommend several things: first, there needs to be moral support from parents to patients, so that the healing process is optimal. Second, the local government must fully support (especially financially) the activities at the pesantren. Third, the community must accept back clients who recover as part of the community.